2005
DOI: 10.1117/12.606874
|View full text |Cite
|
Sign up to set email alerts
|

Tunable antenna-coupled metal-oxide-metal (MOM) uncooled IR detector (Invited Paper)

Abstract: Missile Defense Agency/Advanced Systems, in partnership with both EUTECUS/University of Notre Dame (UND) and ITN Energy Systems/University of Central Florida (UCF) has embarked on developing a multispectral imaging IR sensor. This technology, when matured, could revolutionize IR sensor technology by reducing the need for cooling, eliminating lattice matching and avoiding epitaxial fabrication processes. This paper describes the approaches employed by both EUTECUS/UND and ITN/UCF teams to integrate nano-antenna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Various research groups have investigated thinfilm based MIM diodes for IR detection [1,3,4,[8][9][10][11] and found that MIM diodes with high enough work function difference electrodes exhibit non-linear current-voltage (I-V) behaviour that can produce rectification. They have been fabricated with a wide variety of material combinations like, Al-Al 2 O 3 -Al [12], Cr-CrO-Au [9,13], Al-Al 2 O 3 -Ag [14], Nb-NbOx-Au [13], NiNiO-Au, Ag, Ni, Pt, [4,11,15,16]. In this work Ni-NiO-Cr MIM diodes were fabricated on a Si substrate using standard IC processing technology to exhibit a more pronounced level of non-linearity and asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Various research groups have investigated thinfilm based MIM diodes for IR detection [1,3,4,[8][9][10][11] and found that MIM diodes with high enough work function difference electrodes exhibit non-linear current-voltage (I-V) behaviour that can produce rectification. They have been fabricated with a wide variety of material combinations like, Al-Al 2 O 3 -Al [12], Cr-CrO-Au [9,13], Al-Al 2 O 3 -Ag [14], Nb-NbOx-Au [13], NiNiO-Au, Ag, Ni, Pt, [4,11,15,16]. In this work Ni-NiO-Cr MIM diodes were fabricated on a Si substrate using standard IC processing technology to exhibit a more pronounced level of non-linearity and asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The highest sensitivity is 31 V −1 at 80 mV, which is the highest ever reported for a thin-film MIM tunneling diode. The closest reported value is disclosed in [11]: 13 V −1 . The measurement data, polynomial fitting, and sensitivity of the highest sensitivity diode are shown in Fig.…”
Section: Experiments Resultsmentioning
confidence: 85%
“…However due to a lack of asymmetry, the second Ni electrode must be replaced with a metal of different work function in order to achieve rectification. This has been investigated by Hoofring et al [51], Krishnan et al [52,53] and Esfandiari et al [54] with Au, Cr and Pt contacts respectively, all displaying good asymmetrical I-V response. Other structures of dissimilar materials which have shown promising results are Al/Al2O3/Ni [55,56], Nb/Nb2O5/Pt [57,58,59], ZrCuAlNi/Al2O3/Al [60] and also Nb/Nb2O5/Ag [61].…”
Section: Rectifying Elementmentioning
confidence: 91%